Improved Load Balancing on Software Defined Network-based Equal Cost Multipath Routing in Data Center Network - Ramadhika Dewanto; Rendy Munadi; Ridha Muldina Negara (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Equal Cost Multipath Routing (ECMP) is a routing application where all available paths between two nodes are utilized by statically mapping each path to possible traffics between the source and destination hosts in a network. This configuration can lead to congestion if there are two or more traffics being transmitted into paths with overlapping links, despite the availability of less busy paths. Software Defined Networking (SDN) has the ability to increase the dynamicity of ECMP by allowing the controller to monitor available bandwidths of all links in the network in real-time. The measured bandwidth is then implemented as the basis of the calculation to determine which path traffic will take. In this research, an SDN-based ECMP application that can prevent network congestion was made by measuring the available bandwidth of each available paths beforehand, thus making different traffics transmitted on non-overlapped paths as much as possible. The proposed scheme increased the throughput by 14.21% and decreased the delay by 99% in comparison to standard ECMP when congestion occurs and has 75.2% lower load standard deviation in comparison to round-robin load balancer.